2022
DOI: 10.1002/prop.202200092
|View full text |Cite
|
Sign up to set email alerts
|

Introductory Notes on Non‐linear Electrodynamics and its Applications

Abstract: In 1933-1934 Born and Infeld constructed the first non-linear generalization of Maxwell's electrodynamics that turned out to be a remarkable theory in many respects. In 1935 Heisenberg and Euler computed a complete effective action describing non-linear corrections to Maxwell's theory due to quantum electron-positron one-loop effects. Since then, these and a variety of other models of non-linear electrodynamics proposed in the course of decades have been extensively studied and used in a wide range of areas of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 251 publications
0
26
0
Order By: Relevance
“…For instance, although it still admits plane waves such as φ µ = n µ e ipν σ ν as solutions, linear combinations of plane waves are not solutions. This is very similar to ModMax theories [12][13][14][15] (see [16] for a review) and in fact the action (1.10) can be obtained as the dimensional reduction of the ModMax action [10]. This non-linear and non-analytic structure makes the quantisation of Root-T T deformed theories, as well as of ModMax theories, an outstanding problem.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…For instance, although it still admits plane waves such as φ µ = n µ e ipν σ ν as solutions, linear combinations of plane waves are not solutions. This is very similar to ModMax theories [12][13][14][15] (see [16] for a review) and in fact the action (1.10) can be obtained as the dimensional reduction of the ModMax action [10]. This non-linear and non-analytic structure makes the quantisation of Root-T T deformed theories, as well as of ModMax theories, an outstanding problem.…”
Section: Introductionmentioning
confidence: 54%
“…An important outstanding question is how to quantise Root-T T theories (as well as ModMax theories [12][13][14][15][16]). It might be worth undertaking this study on some particular examples which are integrable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notable examples of NLEDs include the famous Born-Infeld theory [2], a crucial component of String Theory in the study of D-branes [3], that makes sure to keep self energy of point particles finite. Other well studied examples include actions involving various functionals of the field tensor and a nice review for these constructions can be found in [4] and references therein. But the main caveat lies in the problem that a generic NLED in 4d is not conformally invariant, neither is it invariant under Hodge duality rotations.…”
Section: Introductionmentioning
confidence: 99%